Navigating the new era of AI: the future of communications graduates / Muhammad Azril Izuan Ramlan, Nurliyana Kamilah Khairul Anuar and Farah Hazween Amanah - Ramlan, Muhammad Azril Izuan; Khairul Anuar, Nurliyana Kamilah (Universiti Teknologi MARA, Negeri Sembilan, 2023)
As the world rapidly advances into the digital age, powered by groundbreaking technologies such as artificial intelligence (AI), the landscape of various industries continues to transform. Communication, being an essential pillar of societal progress, is no exception. Let’s explore the opportunities and challenges that communications graduates may face in their professional journeys in the era of AI and ever-changing technology. First and foremost, AI has evidently revolutionised the way we communicate, enabling more efficient and personalised interactions across various platforms. Its algorithms have significantly improved the capabilities of virtual assistants and chatbots, making them capable of understanding and responding to human language with remarkable accuracy and context sensitivity. This technology has opened up new avenues for communications professionals to engage with audiences and deliver tailored messages. With AI algorithms becoming increasingly sophisticated, communications graduates can leverage these advancements to create compelling and personalised content at any scale. AI-generated tools can analyse vast amounts of data and generate data-driven insights to inform content strategy, optimise social media campaigns, and even create automated content. This allows communications professionals to focus more on strategy and creativity, while AI handles routine tasks, thereby boosting productivity and efficiency. With the right balance, AI would be beneficial to communications graduates not just personally, but professionally as well.